Transgresión a la memoria y su arquitectura en Machala en la última década. - Gonzabay Marin, Victor Ismael (2015)
For better understanding the present research has been divided into four chapters Chapter one refers to the conception of the art object, whose central theme is about "transgression of memory and architecture in Machala in the last decade." Chapter two focuses on the theoretical basis which is essential to understand the basics of architecture and its evolution in the history of Machala. Chapter three artistic preproduction, where sketches, artistic production, the development of the work and final editing comprising the image of the finished work is evident. In chapter four, it addresses the critical issue of the role of the work in this part, some theories that supported the project.